2020
DOI: 10.4314/tjpr.v19i8.12
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of olibanum essential oil on learning and memory in Aβ1-42-induced Alzheimer’s disease mouse model

Abstract: Purpose: To study the effect of olibanum essential oil (OEO) on learning and memory in Alzheimer’s disease (AD) mouse.Methods: Mice were administered the 42-amino acid form of amyloid β-peptide (Aβ1-42) to induce AD and then treated with OEO at 150, 300, and 600 mg/kg, p.o. for two weeks. Following treatment, the AD mice were assessed by step-down test (SDT), dark avoidance test (DAT), and Morris water maze test (MWM). Blood and brain tissues were collected for biochemical assessments. Gas chromatographymass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…73 Thymol acts as an acetylcholinesterase inhibitor (AchE), this enzyme is used for Ach hydrolysis in the human body, a decrease in AchE content could be beneficial for increasing Ach levels in the brain. 74 Thymol also inhibited butyryl-cholinesterase (BuChE) in a dose-dependent manner. 75 Dietary supplementation with thymol improved brain state by induction of antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase (GPx) respectively and the proportion of phospholipids in the brain of aging rat.…”
Section: Mechanisms Of Action Of Essential Oilsmentioning
confidence: 99%
“…73 Thymol acts as an acetylcholinesterase inhibitor (AchE), this enzyme is used for Ach hydrolysis in the human body, a decrease in AchE content could be beneficial for increasing Ach levels in the brain. 74 Thymol also inhibited butyryl-cholinesterase (BuChE) in a dose-dependent manner. 75 Dietary supplementation with thymol improved brain state by induction of antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase (GPx) respectively and the proportion of phospholipids in the brain of aging rat.…”
Section: Mechanisms Of Action Of Essential Oilsmentioning
confidence: 99%
“…Olibanum in Iranian traditional medicine is called Kundur and is known as a remedy for various memory and learning disorders 15 . Recent in vivo and in vitro studies have demonstrated that boswellic acid may improve memory function in rats 16–19 . The administration of boswellic acid was reported to improve memory impairment induced by lipopolysaccharide in rats 20 .…”
Section: Introductionmentioning
confidence: 99%
“… 15 Recent in vivo and in vitro studies have demonstrated that boswellic acid may improve memory function in rats. 16 , 17 , 18 , 19 The administration of boswellic acid was reported to improve memory impairment induced by lipopolysaccharide in rats. 20 However, to the best of our knowledge, there is no clinical trial that evaluated the effect of Olibanum on memory function.…”
Section: Introductionmentioning
confidence: 99%